The Internal Control Systems integration within the State Network of Internal Control of Public Management in the Ceará state - Helena Correia Vidal, Silvia (2022)
The Federal Constitution of 1988 instituted the Internal Control System (SCI), which must function in all powers and entities, in an integrated manner, in order to ensure the proper application of public resources and to evaluate the goals of the pluriannual plan and the programs budget. The absence of infra-constitutional legislation that establishes a minimum standard of action of internal control in Brazil, led the federation entities to establish their way of acting, making the integration of the SCI difficult. In Ceará, the State Network for Internal Control of Public Management of the state of Ceará (RECIGP) was created, with the mission of promoting the integration of the SCI of state and municipal powers. The objective was to analyze whether the Internal Control Systems that make up the RECIGP worked in an integrated way, based on the characteristics, elements and actions of the Network, from 2018 to 2020. As a theoretical reference, the legal frameworks of the Control System are presented. Internal and concepts of institutionalism and isomorphism of organizations. Documental research of qualitative analysis and exploratory nature was carried out. Data triangulation was used for data collection, with the combination of different methods and sources. The research results revealed that RECIGP’s ICS worked in an integrated way and that the Network's contribution occurred due to the characteristics of its debureaucratized model and without formal structure, aligned with the new institutionalism, by normative isomorphism and by mimetic isomorphism, based on actions continuous training and benchmarking and partnerships between participants.